Nitrogen, Phosphorus, and Sulfur Co-Doped Hollow Carbon Shell as Superior Metal-Free Catalyst for Selective Oxidation of Aromatic Alkanes - Yang, Shuliang; Peng, Li; Huang, Peipei; Wang, Xiaoshi; Sun, Yongbin; Cao, Changyan; Song, Weiguo (Angewandte Chemie International Edition, 2016)
Metal‐free heteroatom‐doped carbocatalysts with a high surface area are desirable for catalytic reactions. In this study, we found an efficient strategy to prepare nitrogen, phosphorus, and sulfur co‐doped hollow carbon shells (denote as NPS‐HCS) with a surface area of 1020 m2 g−1. Using a poly(cyclotriphosphazene‐co‐4,4′‐sulfonyldiphenol) (PZS) shell as carbon source and N, P, S‐doping source, and the ZIF‐67 core as structural template as well as extra N‐doping source, NPS‐HCS were obtained with a high surface area and superhydrophilicity. All these features render the prepared NPS‐HCS a superior metal‐free carbocatalyst for the selective oxidation of aromatic alkanes in aqueous solution. This study provides a reliable and facile route to prepare doped carbocatalysts with enhanced catalytic properties. Highly efficient and selective: A synthetic route was developed to produce nitrogen, phosphorus, and sulfur co‐doped hollow carbon shells which were used as a metal‐free carbocatalyst. The carbocatalyst had a high surface area and showed superior activity in the selective oxidation of aromatic alkanes in aqueous solution.